Multi‐Satellite Tracking of Surface Water Storage Change in the Era of Surface Water and Ocean Topography (SWOT) Satellite Mission - Pritam Das; Faisal Hossain (Earth and Space Science)
Abstract The Surface Water and Ocean Topography (SWOT) satellite, launched in December 2022, represents a significant advancement in the remote sensing of global water bodies, providing simultaneous measurements of Water Surface Elevation (WSE) and extent in all‐weather conditions. This study evaluates SWOT's capability to estimate reservoir storage dynamics in comparison to pre‐SWOT methods. SWOT demonstrates high accuracy in measuring WSE, achieving a median R2 close to 1 and root mean square errors nearly an order of magnitude lower compared to earlier non‐SWOT approaches. SWOT offers substantial improvement over single‐sensor and multi‐sensor methods, due to spatial averaging of distributed elevation measurements, which was further validated by similar measurements of the ICESat‐2 satellite. The key limiting factor in estimating storage from elevation measuring sensors was found to be the accuracy of Area‐Elevation‐Volume curve. Furthermore, preliminary applications of machine learning to integrate SWOT with non‐SWOT data sets show promise, although constrained by limited data availability of SWOT as of late 2024.